PENGARUH FORMULASI AMPAS KENARI (CANARIUM VULGARE SP) TERHADAP KUALITAS ORGANOLEPTIK DAN PROTEIN ABON - Hemy Ratmas Djasibani; Lila Istike Lani (Institute of Computer Science (IOCS), 2026)
Walnut trees grow abundantly in eastern Indonesia, such as North Sulawesi, Maluku, Seram, and Alor Island. Walnut pulp is a byproduct of walnut oil processing. Walnut pulp can be made into a nutritious food product due to its high protein, carbohydrate, and water content. The purpose of this study was to determine the effect and best formulation of walnut pulp on the organoleptic and protein quality of shredded meat. The method used was a completely randomized design (CRD) experiment with four treatments and three replications, resulting in 12 experimental units. The results showed that Treatment D (formulation using 200 grams of walnut pulp) was highly preferred by consumers, with an average color score of 3.59%, flavor 3.57%, aroma 4%, and texture 3.53%. The highest protein content (%) was found in Treatment D (formulation using 200 grams of walnut pulp), at 7.77%.